A Comparative Approaches of Juvenile Delinquency in India and China (International Journal of Food and Nutritional Sciences, 2022)
Juvenile delinquency is a pressing issue in both India and China, shaped by rapid urbanization, economic inequality, and shifting societal norms. This comparative study highlights the differences and similarities in how these nations address juvenile crime through legal and rehabilitative frameworks. India’s Juvenile Justice (Care and Protection of Children) Act 2015 prioritizes rehabilitation and reintegration, following a welfare-based model centered on the best interests of the child. However, the Indian system struggles with limited resources, overwhelmed courts, and uneven implementation across states. Despite this, India’s approach remains rehabilitative and child-focused.